Site-selective arylations of nature-inspired flavonoids or steroidal phenols via C—H or O—H activation - Rebeka Ignácz; Noémi Bózsity; Dénes Unger; Zoltán Kele; István Zupkó; Attila Hunyadi; Marija Gjorgoska; Tea Lanišnik Rižner; Erzsébet Mernyák (Journal of Enzyme Inhibition and Medicinal Chemistry)
Phenols are important structural elements of natural products and pharmaceuticals. Due to their versatile chemical transformability, phenols are frequently used building blocks in medicinal chemistry. Their aromatic nature allows directed C(sp2)—H functionalisations, especially at the ortho positions. In contrast, meta substitutions are less well known. As a continuation of our recently described metal-catalysed cross couplings, here we report arylations of two nature-inspired phenol derivatives via C—H or O—H activation. A directing group (DG) was introduced onto C-3-O of 13α-oestrone, and the resulting carbamate was subjected to Cu(II)-catalysed meta arylation using diaryliodonium triflates as reagents. As a result, C-1-arylated derivatives were obtained. The arylation of the 1’-O-butyl protoapigenone proceeded regioselectively at C-5-O. The 1-(4-tert-butylphenyl)-13α-oestrone carbamate and all O-arylated protoflavones substantially inhibited the growth of the applied human cancer cell lines and exerted proapoptotic activity on HeLa cells. The 1-(4-tert-butylphenyl)-13α-oestrone proved to be a potent 17β-HSD1 inhibitor.